2020
DOI: 10.3390/agriculture10080353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pigments, Phenolic and Volatile Compounds, and Antioxidant Activity of a Spontaneous Population of Portulaca oleracea L. Grown in Tunisia

Abstract: Portulaca oleracea L., commonly known as purslane, is a weed with worldwide distribution and considerable medicinal uses due to its high levels of phytochemical compounds. However, until now, few studies have been conducted on the biochemical characterization of P. oleracea grown in Tunisia, a possible area of its origin as other North African countries. Therefore, the aim of the present study was to determine the phytochemical composition and antioxidant potential of leaves and stems from a Tunisian spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 69 publications
3
11
1
1
Order By: Relevance
“…As expected, considering the phytochemical traits, a high correlation of TPC was detected with antioxidant activity, measured using both the DPPH and FRAP assays. This is in agreement with previous results for other crops [50,51].…”
Section: Correlationssupporting
confidence: 94%
“…As expected, considering the phytochemical traits, a high correlation of TPC was detected with antioxidant activity, measured using both the DPPH and FRAP assays. This is in agreement with previous results for other crops [50,51].…”
Section: Correlationssupporting
confidence: 94%
“…The plant P. oleracea L. (purslane) has been reported to have a rich chemical composition mainly flavonoid, terpenoids, alkaloid, and organic acid (Dabbou et al, 2020). Additionally, fatty acids, terpenoids, vitamins, polysaccharides, proteins, sterols, and vitamins have also been found in purslane (Petropoulos et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown the utilization of purslane extract as antioxidant, anti-inflammation, antitumor and anti-bacteria. 23,24,25,26,27 The chemical content of common purslane ethanol extract includes alkaloid, flavonoid, terpenoid, vitamin, and mineral. The antioxidant content in purslane ethanol extract against free radical formed by reacting with the free radicals stabilizes free radicals and changes free radicals into non-reactive compounds.…”
Section: Resultsmentioning
confidence: 99%